Development, evaluation, and influence of formulation and process variables on in vitro performance of oral elementary osmotic device of atenolol - Arjun, N.; Narendar, D.; Sunitha, K.; Harika, K.; Nagaraj, B. (International Journal of Pharmaceutical Investigation)
Purpose: Osmotic devices are the most promising strategy-based systems for controlled drug delivery. By optimizing formulation and processing parameters, possible to develop osmotic systems to deliver drugs at predetermined rate with high in vitro‑in vivo correlation. The aim of the present investigation was to develop an oral elementary osmotic pump (EOP) of atenolol with zero‑order or near zero‑order drug release profile. Materials and Methods: Differential scanning calorimetry and Fourier transform-infrared spectroscopy studies did not show any evidence of interaction between the drug and excipients. Formulations were prepared by wet granulation method and coated with cellulose acetate (CA)/ethyl cellulose containing varying amounts of dibutyl phthalate (DBP)/poly (ethylene glycol)-400 as a plasticizer. The effect of different formulation variables on drug release: type and concentration of osmogen and plasticizer, size of the delivery orifice, nature of the rate controlling membrane, and membrane weight gain were studied. The release studies also compared with marketed immediate release formulation. Results: Formulations containing NaCl, mannitol, and combination of both as osmogens in the drug:osmogen ratio of 1:3 and 1:4 showed zero-order drug release. Marketed tablet releases more than 95% drug in different media in 90 min. The 4% CA in acetone with DBP as a plasticizer (at a concentration of 15% w/w of polymer), with orifice diameter 565 µm, and 8.05% increase in weight on coating were found to control the drug release independent of pH and agitational intensity. The formulations were stable for 3 months as per the International Council for Harmonisation guidelines. Conclusion: Atenolol containing EOPs and process parameters on release studies were studied and confirmed based on osmotic technology.
Keywords: Atenolol; drug release; elementary osmotic pump; formulation variables; marketed tablet; osmogen